Molecular characterization of the Rpt1/p48B ATPase subunit of the Drosophila melanogaster 26S proteasome. - Szabó, A.; Pál, M.; Deák, P.; Kiss, P.; Ujfaludi, Z.; Pankotai, T.; Lipinszki, Z.; Udvardy, A. (Molecular Genetics and Genomics, 2007)
The function and the molecular properties of the Rpt1/p48B ATPase subunit of the regulatory particle of the Drosophila melanogaster 26S proteasome have been studied by analyzing three mutant Drosophila stocks in which P-element insertions occurred in the 5'-non-translated region of the Rpt1/p48B gene. These P-element insertions resulted in larval lethality during the second instar larval phase. Since the Rpt1/p48B gene resides within a long intron of an annotated, but uncharacterized Drosophila gene (CG17985), the second instar larval lethality may be a consequence of a combined damage to two independent genes. To analyze the phenotypic effect of the mutations affecting the Rpt1/p48B gene alone, imprecise P-element excision mutants were selected. One of them, the pupal lethal P1 mutation, is a hypomorphic allele of the Rpt1/p48B gene, in which the displacement of two essential regulatory sequences of the gene occurred due to the insertion of a 32 bp residual P-element sequence. This mutation caused a 30-fold drop in the cellular concentration of the Rpt1/p48B mRNA. The decline in the cellular Rpt1/p48B protein concentration induced serious damage in the assembly of the 26S proteasomes, the accumulation of multiubiquitinated proteins, a change in the phosphorylation pattern of the subunit and depletion of this ATPase protein from the chromatin.